For the love of renovating : tips, tricks & inspiration for creating your dream home - Bordelon, Barry; Slocum, Jordan (Union Square & Co., 2024)
"For the Love of Renovating is the book every fixer-upper needs. Jordan and Barry-aka the Brownstone Boys-are the go-to renovation team for historic brownstones and other older homes that need a little TLC. In their debut book, they walk readers through the entire process of renovating a house, starting with things to consider before you've made an offer, followed by guidance on developing a design, a schedule, and budgeting; they end by giving a room-by-room tour that includes helpful tips and inspiration. Throughout the book, beautiful photos and Renovation Recipes give the ingredients and step-by-step instructions for turning the house you have into the house you love"--